A tail of labor supply and a tale of monetary policy - Cristiano Cantore; Filippo Ferroni; Haroon Mumtaz; Angeliki Theophilopoulou (Federal Reserve Bank of Chicago, 2022)
We study the interaction between monetary policy and labor supply decisions at the household level. We uncover evidence of heterogeneous responses and a strong income effect on labor supply in the left tail of the income distribution, following a monetary policy shock in the US and the UK. That is, while aggregate hours and labor earnings decline, employed individuals at the bottom of the income distribution increase their hours worked in response to an interest rate hike. Moreover, their response is stronger in magnitude relative to other income groups. We rationalize this using a two-agent New-Keynesian (TANK) model where our empirical findings can be replicated with a lower intertemporal elasticity of substitution for the Hand-to-Mouth households. This setup has important implications for the impact of inequality on the transmission of monetary policy. We unveil a novel dampening effect on aggregate demand generated by the Hand-to-Mouth substitution of leisure for consumption following a negative income shock. Therefore we show that the impact of inequality on the transmission mechanism of monetary policy is highly dependent on the different layers of heterogeneity on the household side and the different combinations of nominal and real frictions. More inequality does not necessarily generate a stronger response of aggregate demand after a monetary policy shock.
Keywords: E52; E32; C10; 330; Monetary policy; Household Survey; FAVARs; TANK; Hand to Mouth